The Effect of Sterilization Procedures and Different Irrigation Solutions on Surface Roughness of Nickel-Titanium Files: An Atomic Force Microscopy Study - Elmali, Enes; Oztekin, Faruk (Harran Üniversitesi, 2026)
Background: The present study aimed to assess how different irrigation solutions and sterilization procedures influence the surface morphology of ProTaper Next (PTX) and Reciproc Blue (RB) Nickel-Titanium (NiTi) endodontic instruments. Materials and Methods: Sixty rotary NiTi files were evaluated-thirty PTX and thirty RB. Each instrument system was randomly divided into five subgroups (n=6). Three groups were dynamically immersed for 5 minutes in 5.25% sodium hypochlorite (NaOCl), BioAKT, or 18% etidronic acid (HEBP). Another group was exposed to five consecutive autoclave sterilization cycles, while one subgroup served as the untreated control. Surface characterization was performed using atomic force microscopy (AFM) operated in tapping (non-contact) mode. Five random sites within the apical 3 mm of each sample were scanned over a 5 μm × 5 μm area. Three-dimensional surface profiles were processed with XEI software to determine the root mean square (RMS) roughness and depth parameters. Statistical analyses were carried out using the Kolmogorov-Smirnov test, one-way ANOVA, and post hoc LSD test, with the level of significance set at p Conclusions: Exposure to NaOCl, etidronic acid, BioAKT, and autoclave sterilization significantly increased the surface roughness of PTX and RB NiTi files. Among all tested conditions, HEBP and repeated sterilization produced the most pronounced alterations in surface parameters.
Keywords: BioAKT; etidronic acid; surface analysis; atomic force microscopy; ProTaper next; reciproc blue